Pengaruh Video Animasi Terhadap Hasil Belajar Kognitif Pada Mata Pelajaran IPS Materi Menghargai Jasa Pahlawan di Kelas V SDN Sidokumpul Sidoarjo - Kartika Ayuningsih (JICTE (Journal of Information and Computer Technology Education), 2017)
Based on the observation that have been done by the research, the learning process in SDN Sidokumpul Sidoarjo is monotonous without using media. Many of students get the score below the minimum criteria of mastery learning (76) in social science. Related to the problem, so the research conduct the study with the purpose to repaired the cognitive learning result in social study by using animation video media. The study use cuantitative experimental design, One-Group Pretest-Posttest. The subject of this study is grade V class C consist of 25 students. Sampling technic  that is used is purposive sampling. The data collection use test sheets are pretest and posttest. The result of this study are 56,32 (average of  pretest) and 83,92 (average of posttest). Including animation video affect to the cognitive learning result in social science the material menghargai jasa pahlawan in class V SDN Sidokumpul Sidoarjo. Then in the N-gain calculation is obtained result 0,63 that is chased the level of criteria is medium.